Reply to Chen et al.: Parametric methods for cluster inference perform worse for two‐sided t‐tests. Issue 5 (7th December 2018) - Eklund, Anders; Knutsson, Hans; Nichols, Thomas E.
Abstract: One‐sided t ‐tests are commonly used in the neuroimaging field, but two‐sided tests should be the default unless a researcher has a strong reason for using a one‐sided test. Here we extend our previous work on cluster false positive rates, which used one‐sided tests, to two‐sided tests. Briefly, we found that parametric methods perform worse for two‐sided t ‐tests, and that nonparametric methods perform equally well for one‐sided and two‐sided tests.